Multisensor, Microseismic Observations of a Hurricane Transit Near the ALOHA Cabled Observatory. Issue 4 (20th April 2018) - Butler, Rhett; Aucan, Jérome
Abstract: The generation of microseisms is investigated at the ALOHA Cabled Observatory (ACO) north of Oahu during the close passage of Hurricane Lester in September 2016. Sensors include a seafloor ALOHA pressure gauge at ACO, KIP seismic data on Oahu, and nearby wave buoys. Examination of frequency‐direction spectra from wave buoys and numerical wave model outputs confirms two separate microseism generation processes: At frequencies <0.225 Hz, the microseisms are generated by swells from Hurricane Lester and Typhoon LionRock traveling in opposite directions in the vicinity of ALOHA. At higher frequencies >0.225 Hz, microseisms are dominated by waves originating from Hurricane Lester. The cross‐over frequency (0.225 Hz) occurs where the ocean wave group velocity matches the Hurricane storm track speed. Correcting for impedance, the spectrogram for energy at ALOHA closely correlates with KIP. When opposing swells meet at a distance from the Hurricane Lester and ACO, the resulting microseisms also spread geometrically in propagation to ALOHA and KIP, effectively equivalent to 1/R 2 . At the microseism peak, 4 September, the dominant motions of KIP are observed with retrograde particle motion characteristic of Rayleigh modes, in both the radial‐vertical and transverse‐vertical sagittal planes at distances of ≲400 km from the eye. Otherwise, the energy on the transverse component is comparable to the radial component. We hypothesize that the observed transverse energy arises locally: (1) from the extended microseism source region near ACO and (2) and from scattering by dipping structure and anisotropy embedded in the crust during emplacement at the Pacific‐Farallon ridge. Plain Language Summary: The close passage of Hurricane Lester near the Hawaiian Islands in September 2016 afforded an in‐depth, close‐up study of storm generation of the largest background vibrations observed planet wide. The observations at the ALOHA Cabled Observatory on the seafloor below the Hurricane, coupled with seismic sensors on Oahu, and ocean wave buoys off shore, present a detailed picture connecting the storm to the ocean and Earth. Wave interactions from a distant typhoon near Japan play an important role. Vibration energy levels observed on Oahu closely match those on the sea floor 100 km north of Oahu, where ALOHA Cabled Observatory is the world's deepest seafloor observatory at 4, 728 m depth. Characteristic vibrations generated radially from the Hurricane were observed, along with unexpected transverse motions perpendicular to the radial waves. This latter observation is consistent with a broad source region extending from Hurricane Lester and generating the vibrations. Evidence for substantial scattering of the vibrations in the ocean crust is inferred, due to slanting layers and directionally varying velocities, dating back nearly 80 million years ago when the sea floor was being originally being emplaced at a Pacific mid‐ocean ridge. This hurricane transit yields new knowledge on how storms vibrate the planet. Key Points: Microseisms are observed and mapped from the interaction of Hurricane Lester near Hawaii and Typhoon LionRock near Japan Dominant radial‐vertical and transverse‐vertical motions show retrograde particle motions characteristic of Rayleigh wave Observed transverse motions may arise from a broad source region with local scattering in the crust emplaced at the Pacific‐Farallon ridge